Manilkara zapota (L.) P. Royen: potential source of natural antioxidants - Mohd Tamsir, Norain; Mohd Esa, Norhaizan; Che Omar, Siti Nursalwah; Shafie, Nurul Husna (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Manilkara zapota (L.) P. Royen or sapodilla is a fruit-bearing tree that has been cultivated mainly in tropical areas including Mexico and South East Asia. The fruits and the other parts of M. zapota plant have been used since ages ago for various medicinal purposes. However, the data on the antioxidant properties of various parts of M. zapota is limited. Therefore, we aimed to measure the content and capacity of antioxidants in various M. zapota plant parts and also to screen the phytoconstituents present in the part with the highest antioxidant content and capacity. Methods: The in vitro antioxidant evaluation including the content of total phenolic (TPC) and total flavonoids (TFC) as well as β-carotene bleaching and 1-diphenyl-2-picrylhydrazyl (DPPH) scavenging ability of the leaves, seeds, flesh, and peels of M. zapota extracted by aqueous and ethanol were determined. The plant part that exhibited the highest TPC, TFC, and antioxidant capacity was selected for phytoconstituents identification using liquid chromatography mass spectrometry. Results: M. zapota leaves aqueous extract exhibited the highest TPC, TFC, and antioxidant capacities and therefore selected for phytoconstituents identification. Our study provide additional data in which a total of 39 phytoconstituents have been identified in the M. zapota leaves including m-coumaric acid, quinic acid, robinetinidol-4alpha-ol, isoorientin 6’’-O-caffeate, apocynin A, and C16 Sphinganine. Conclusion: Thus, our study revealed that M. zapota leaves aqueous extract has potential as a promising naturally-occurring antioxidant candidate which could be useful for medicinal and nutritional functions.